Analysis of the Influence of Profit Management and Financial Performance on Company Value: Empirical Study on Non-Financial State-Owned Companies Period 2019 – 2023 - Aditia Sepdiansyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to obtain empirical evidence about influence earnings management and financial performance on company value listed on the Indonesian Stock Exchange (BEI) in the 2019-2023 period. The data used in this research is secondary data. Analysis of research data using multiple linear regression with the help of IBM SPSS 25 program. The independent variables in this research are earnings management and financial performance. And, the dependent variable in this research is company value. Using the purposive sampling method as a sampling technique sample, so that a population of 80 companies is obtained. In this research,24 non-financial state-owned companies were used as samples. For know the magnitude of the influence of earnings management and financial performance used regression analysis, correlation analysis F test and t test and coefficient analysis determination. The results of this study indicate that the variables are variable Earnings management does not have a significant effect on company value. meanwhile, financial performance significant positive effect on company value.